Contrast-enhanced ultrasound and shear wave elastography in the diagnosis of ACR TI-RADS 4 and 5 category thyroid nodules coexisting with Hashimoto’s thyroiditis - Wang, Bin; Ou, Xiaoyan; Yang, Juan; Zhang, Haibo; Cui, Xin-Wu; Dietrich, Christoph F.; Yi, Ai-Jiao (Frontiers in Oncology, 2023)
Objective: To evaluate the value of contrast-enhanced ultrasound (CEUS), shear wave elastography (SWE) and their combined use in the differentiation of American College of Radiology (ACR) thyroid imaging reporting and data system (TI-RADS) 4 and 5 category thyroid nodules coexisting with Hashimoto’s thyroiditis (HT). Materials and Methods: A total of 133 pathologically confirmed ACR TI-RADS 4 and 5 category nodules coexisting with HT in 113 patients were included, CEUS and SWE were performed for all nodules. The sensitivity, specificity, negative predictive value (NPV), positive predictive value (PPV), accuracy and the area under the receiver operating characteristic curve (AUC) of the SWE, CEUS and combined use of both for the differentiation of benign and malignant nodules were compared, respectively. Results: Using CEUS alone, the sensitivity, specificity, PPV, NPV and accuracy were 89.2%, 66.0%, 81.3%, 78.6% and 80.5%, respectively. Using SWE alone, Emax was superior to Emin, Emean, Eratio to the benign and malignant nodules with the best cutoff Emax > 46.8KPa, which had sensitivity 65.1%, specificity 90.0%, PPV 91.5%, NPV 60.8% and accuracy 74.4%, respectively. Compared the diagnostic performance of qualitative CEUS or/and quantitative SWE, combination of CEUS and SWE had best sensitivity, accuracy and area under curve (AUC), the sensitivity, specificity, PPV, NPV, accuracy and AUC were 94.0%, 66.0%, 82.1%, 86.8%, 83.5% and 0.80 (95% confidence interval [CI], 0.713, 0.886), respectively. Conclusion: In conclusion, CEUS and SWE were useful for the differentiation of benign and malignant ACR TI-RADS 4 and 5 category thyroid nodules coexisting with HT. Combination of CEUS and SWE could improve the sensitivity and accuracy, compared with using CEUS or SWE alone, it could be a non-invasive, reliable and useful method to differentiate benign from malignant ACR TI-RADS 4 and 5 category thyroid nodules coexisting with HT.